Adapting a family-involved intervention to increase initiation and completion of evidenced-based psychotherapy for posttraumatic stress disorder - Megan Shepherd-Banigan; Stephanie Y. Wells; Margaret Falkovic; Princess E. Ackland; Cindy Swinkels; Eric Dedert; Rachel Ruffin; Courtney H. Van Houtven; Patrick S. Calhoun; David Edelman; Hollis J. Weidenbacher; Abigail Shapiro; et al. (Elsevier, 2022)
Posttraumatic stress disorder (PTSD) is disabling condition among United States Veterans. Training programs for evidenced-based therapies have been rolled out nationally in the Veterans Health Administration (VHA), but provider adoption of these treatments is limited and rates of Veteran dropout are high. Increasing support for mental health therapy within the Veteran's social network would improve treatment engagement. We discuss the adaptation of Recovery-Oriented Decisions for Relatives' Support (REORDER)-a family-based intervention for individuals with serious mental illness- to create Family Support in Mental Health Recovery (FAMILIAR), an intervention that seeks to strengthen support partners' abilities to help Veterans engage in therapy. Our goal was to apply modifications to meet the needs of Veterans with PTSD and their support partners. We used input from Veterans, support partners, clinicians and VA system leaders to inform the modifications. Then, a multi-disciplinary intervention development team met to determine which modifications would be applied and how. We used the domains from the Framework for Adaptations and Modification (FRAME) to systematically track and describe modifications. Adaptations made to REORDER included changes in content, structure, and delivery format. The resulting intervention, FAMILIAR, was a 3-4 session intervention beginning prior to EBP initiation and continuing through sessions 3, 4 or 5 of the EBP. Sessions were designed for maximum flexibility and could be offered either in-person or virtually, and sessions involve interactions between the interventionist with the Veteran and support partner alone and together. We learned the importance of including diverse stakeholder perspectives to develop a comprehensive understanding of the needs of the target population and the health system. While feasibility and effectiveness testing is needed, we applied a proactive adaptation approach that we anticipate will make FAMILIAR successful in addressing patient, clinical, and system considerations of a family approach to increase Veteran engagement in PTSD treatment.